162k views
0 votes
Can anyone please help me with these

Evaluate the following expression
4(×+2)=
3 (a+2)=
2 (×+3)=

User Sitram
by
5.6k points

2 Answers

2 votes

Explanation:

Use the distributive property a(b + c) = ab + ac

4(x + 2) = (4)(x) + (4)(2) = 4x + 8

3(a + 2) = (3)(a) + (3)(2) = 3a + 6

2(x + 3) = (2)(x) + (2)(3) = 2x + 6

User Derek Sonderegger
by
5.0k points
4 votes

Answer:

4(x+2) = 4*x + 4*2 = 4x+8

3(a+2) = 3*a + 3*2 = 3a + 6

2(x+3) = 2*x + 2*3 = 2x +6

Hope this help you :3

User Michal Pravda
by
5.3k points